Old Dogs Learning New Tricks? The Effect of Age and Generation on Shopping Behaviour - Heli Marjanen; Anna-Maija Kohijoki; Kaisa Saastamoinen; Janne Engblom (Taylor & Francis, 2022)
Previous research has shown that both age and generational cohort membership affect shopping orientation and store choice criteria, although the results are mixed. This study applied a longitudinal research setting to investigate the choice orientations of six generational cohorts and seven age groups, respectively, in the context of non-grocery shopping trips. The study was based on data collected through four household surveys conducted in the Turku area, Finland, over 17 years. An exploratory factor analysis was used to identify six choice orientation dimensions that appeared as sufficiently similar in all four cross-sectional surveys. The results show that although both age and generation, if used as sole independents in a model, only explain 0.1 to 13 per cent of the variation between the categories (one-way ANOVA), in most cases, the differences are statistically significant. Age performed slightly better when the models were run for each year separately. However, in line with the underlying assumption of the generational theory, the relative importance attached to each of the choice orientation dimensions in early adulthood remained somewhat stable when the generational cohorts aged.